Komunikasi Organisasi Kemahasiswaan di Kota Mataram - Ni Nyoman Puji Artini (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This research examines the communication of student organizations carried out by the Student Executive Board of the Gde Pudja Mataram State Hindu Institute (BEM IAHN Gde Pudja Mataram) in 2020-2021. The formulation of the research problem, namely: (1) How is the organizational communication implementation of BEM IAHN Gde Pudja Mataram in 2020-2021?; (2) What is the organizational communication function of BEM IAHN Gde Pudja Mataram in 2020-2021?; (3) What is the impact of Gde Pudja Mataram's BEM IAHN organizational communication in 2020-2021? This study uses qualitative interpretive methods. Data was collected using observation techniques, interview techniques and documentation techniques. Data were analyzed qualitatively with data reduction, display, and verification steps. The results of data analysis are presented using narrative text with the help of sharpening it with relevant theories. Testing the validity of the data is done by pushing the credibility of the data, data transferability and data confirmability. The results showed four organizational communications implemented by BEM IAHN Gde Pudja Mataram: building a common understanding, implementing persuasive steps, creating work awareness through motivation, and communicating action through social activities. There are several communication functions of BEM IAHN Gde Pudja Mataram: regulatory, persuasive, educative, and social. The organizational communication of BEM IAHN Gde Pudja Mataram has the effect of increasing work motivation, creating satisfaction in creativity, building morale and improving performance results.